CRABP1, C1QL1 and LCN2 are biomarkers of differentiated thyroid carcinoma, and predict extrathyroidal extension - Ricardo Celestino; Torfinn Nome; Ana Pestana; Andreas M. Hoff; A. Pedro Gonçalves; Luísa Pereira; Bruno Cavadas; Catarina Eloy; Trine Bjøro; Manuel Sobrinho-Simões; Rolf I. Skotheim; Paula Soares (BMC Cancer, 2018)
Abstract Background The prognostic variability of thyroid carcinomas has led to the search for accurate biomarkers at the molecular level. Follicular thyroid carcinoma (FTC) is a typical example of differentiated thyroid carcinomas (DTC) in which challenges are faced in the differential diagnosis. Methods We used high-throughput paired-end RNA sequencing technology to study four cases of FTC with different degree of capsular invasion: two minimally invasive (mFTC) and two widely invasive FTC (wFTC). We searched by genes differentially expressed between mFTC and wFTC, in an attempt to find biomarkers of thyroid cancer diagnosis and/or progression. Selected biomarkers were validated by real-time quantitative PCR in 137 frozen thyroid samples and in an independent dataset (TCGA), evaluating the diagnostic and the prognostic performance of the candidate biomarkers. Results We identified 17 genes significantly differentially expressed between mFTC and wFTC. C1QL1, LCN2, CRABP1 and CILP were differentially expressed in DTC in comparison with normal thyroid tissues. LCN2 and CRABP1 were also differentially expressed in DTC when compared with follicular thyroid adenoma. Additionally, overexpression of LCN2 and C1QL1 were found to be independent predictors of extrathyroidal extension in DTC. Conclusions We conclude that the underexpression of CRABP1 and the overexpression of LCN2 may be useful diagnostic biomarkers in thyroid tumours with questionable malignity, and the overexpression of LCN2 and C1QL1 may be useful for prognostic purposes.